2019
DOI: 10.1044/2019_pers-sig19-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Three-/Four-Dimensional Ultrasound Technology in Speech Research

Abstract: Purpose Speech production is a complex 3-dimensional (3D) process, and yet most of what is known about it is derived from 2D midsagittal data. The relatively recent development of safe 3D imaging technologies (including magnetic resonance imaging and ultrasound) provide new opportunities to revisit and reformulate what is already known and to push the boundaries of current knowledge still further. A particularly useful imaging modality for this purpose is 3D/4D ultrasound, which until very recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…While 2D ultrasound has been widely used in phonetics research for many years (e.g., Gick 2002, Davidson 2002, Miller & Finch 2011, Proctor 2011, Zharkova 2013, Mielke 2015, Boyce et al 2016, Al-Tairi et al 2017, Strycharczuk & Scobbie 2017, Turton 2017, Ahn 2018, Bennett et al 2018, Tabain & Beare 2018, 3D/4D ultrasound is a relatively new technology that was originally used in speech and swallowing research by Chi-Fishman et al (2000), Bressmann et al (2007), and Bressmann (2010). Modern 3D/4D ultrasound equipment, described by Lulich et al (2018) and Lulich & Pearson (2019), has recently been used to study liquid sound articulation in American English (Berkson et al 2017), South Korean (Hwang et al 2019a;Hwang et al 2019b), and Brazilian Portuguese (Charles & Lulich 2018, 2019, as well as tongue dorsum and tongue root articulation in Arabic (Mokh et al, 2020) and Polish (Cavar et al 2017;Lulich et al 2017;Cavar et al 2020).…”
Section: Data Collectionmentioning
confidence: 99%
“…While 2D ultrasound has been widely used in phonetics research for many years (e.g., Gick 2002, Davidson 2002, Miller & Finch 2011, Proctor 2011, Zharkova 2013, Mielke 2015, Boyce et al 2016, Al-Tairi et al 2017, Strycharczuk & Scobbie 2017, Turton 2017, Ahn 2018, Bennett et al 2018, Tabain & Beare 2018, 3D/4D ultrasound is a relatively new technology that was originally used in speech and swallowing research by Chi-Fishman et al (2000), Bressmann et al (2007), and Bressmann (2010). Modern 3D/4D ultrasound equipment, described by Lulich et al (2018) and Lulich & Pearson (2019), has recently been used to study liquid sound articulation in American English (Berkson et al 2017), South Korean (Hwang et al 2019a;Hwang et al 2019b), and Brazilian Portuguese (Charles & Lulich 2018, 2019, as well as tongue dorsum and tongue root articulation in Arabic (Mokh et al, 2020) and Polish (Cavar et al 2017;Lulich et al 2017;Cavar et al 2020).…”
Section: Data Collectionmentioning
confidence: 99%
“…Using coronal ultrasound imaging, Bressmann et al (2010) found that English speakers had a greater amount of movement for the center of the tongue than the sides, proposing that the observation supported lateral bracing. More recently, Lulich & Pearson (2019) examined the production of an English phrase by superimposing ultrasound coronal tongue images with the equivalent MRI coronal plane image of the articulations. After alignment they were able to demonstrate lateral tongue bracing for /t/ with the sides of the tongue making contact with the palate and upper teeth (Lulich & Pearson 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Lulich & Pearson (2019) examined the production of an English phrase by superimposing ultrasound coronal tongue images with the equivalent MRI coronal plane image of the articulations. After alignment they were able to demonstrate lateral tongue bracing for /t/ with the sides of the tongue making contact with the palate and upper teeth (Lulich & Pearson 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation